Comparative study of mouthparts of the female of two species of Dasybasis Macquart from Chile (Diptera: Tabanidae) - González, Christian R.; Brevis, Karina; Miranda, Carmen; Sotomayor, Arlen (Zootaxa, 2005)
Mouthparts of the female of two species representing Dasybasis Macquart were examined by scanning electron microscopy, and their structures are herein described. The morphology of mouthparts of these species suggests a haematophagous feeding habit. Females of D. senilis (Philippi) and D. testaceomaculata (Macquart) have mandibles with marginal teeth developed and lacinia and labrum with teeth and microteeth.